Opportunity Recognition Amongst Start-Up Entrepreneurs - Shih, Tsung-Jen (2008)
This paper focuses on the issues of opportunity recognition among start-up entrepreneurs. The attitudes and methods of nascent entrepreneurs are assessed via a literature review and the conclusion of four separate case studies. This paper also examines the processes of opportunity recognition in order to establish strategies for entrepreneurs who would like to establish a new venture, by making profits from exploiting the available opportunities. Based on recent and high ranking academic research and deeply interviewed case studies, this paper concludes that several crucial elements cause large influences in opportunity recognition. These elements can provide practical strategies from multiple perspectives to entrepreneurs to implement opportunity recognition processes in exploiting suitable opportunities for them.